Late mortality of long-term survivors of childhood cancer - Krawczuk-Rybak, Maryna (Contemporary Oncology/Współczesna Onkologia, 2011)
In the last four decades there has been enormous progress in the treatment for childhood cancer; the present 5-year survival rate is estimated to be 80%. The increased population of cancer survivors gives us the possibility to assess life quality as well as the late effects of anticancer treatment. In multicentre studies, it has been shown that 60% of survivors have at least one late effect, and one third experience severe or life-threatening sequelae. Survivors of childhood cancers are at risk of recurrence of primary malignancy, development of second cancer and chronic disease of the respiratory and cardiovascular system, which increase the mortality rate. Other late complications, such as diseases affecting kidneys, digestive system or bones, and hormonal and metabolic disturbances lead to deterioration of life quality. This report presents treatment-related factors that increase mortality of cancer survivors by contributing to the development of second cancers, cardiotoxicity or pulmonary complications.